Guia visual de higiene ocupacional: práticas essenciais NHO 05 e NHO 06 - Lenz, Humberto (Brasil, 2025)
This guide was developed in an illustrative and intuitive way with the purpose of presenting and contributing to the understanding of the assessment of occupational exposure to X-rays in radiology services (NHO 05), as well as the assessment of occupational exposure to heat (NHO 06). In this sense, forms of occupational exposure assessment related to each NHO will be presented, as well as a deeper understanding of these standards and their specificities. In view of this, it is important to study these standards, since in addition to the professionals who work in the area of occupational hygiene mentioned, this material also has as its main objective to provide knowledge about these standards to all audiences and guide students on the Occupational Safety course on safety and health at work and occupational risks arising from exposure to heat and X-Rays in radiology services expressed, respectively, in NHO 06 and NHO 05. Therefore, it is estimated that the general public of this work understands the basic concepts of occupational hygiene standards protected in this guide in a practical and beneficial way, so that they can use this study material in a complementary way to current legislative standards, as well as a form of support in their professional activities and in the academic environment.